PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA PETANI TERHADAP TINGKAT PENDIDIKAN ANAK DI DESA BUGBUG, KARANGASEM - Utami, Ni Kadek Mita Setia; Arka, Sudarsana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023DO - 10.24843/EEB.2023.v12.i10.p17, 2023)
Education is one of the most important factors in the development of a country. The purpose of this study was to analyze the effect of family income, age of parents, education of parents, number of dependents, and the level of availability of learning facilities partially and simultaneously on the educational expectations of children of farming families in Bugbug Village, Karangasem District, Karangasem Regency. The data collection technique in this study used purposive sampling with a total sample of 84 people. The analytical technique used is Moderated Regression Analysis (MRA). The results showed that family income, age of parents, education of parents, number of dependents, and the level of availability of learning facilities partially and simultaneously affected the educational expectations of children of farming families in Bugbug Village, Karangasem District, Karangasem Regency. Availability of learning facilities moderates the relationship between family income and the level of educational expectations of farmers' children.